Taxes and the choice of organizational form by entrepreneurs in Sweden - Karin Edmark; Roger Gordon (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
This paper estimates the role of both tax and non-tax determinants in the choice in Sweden to be a closely-held corporation vs. a proprietorship, using individual data for 2004 to 2008 on owners of closely-held businesses. While lower-income individuals face relatively neutral incentives, higher income individuals face strong tax incentives to be corporate. The data suggest a relatively strong correlation between these tax incentives and the likelihood that a firm is corporate. Many conventional non-tax determinants are confirmed in the data as well.
Keywords: G32; H25; G38; 330; self-employment; entrepreneurship; taxation of closely-held businesses; business organizational form